Renal dysfunction as a predictor of recurrence and prognosis in colorectal cancer - Xuekang Ren; Shaogong Zhu; Rongzhen Li; Yunzhan Xia (Frontiers in Oncology)
PurposeThis study explores the relationship between eGFR and recurrence and prognosis in patients with colorectal cancer (CRC).MethodsPatients first diagnosed with CRC at Zhengzhou People’s Hospital between 2018 and 2021 with a median follow-up of 715 days were studied. Demographics, disease characteristics, kidney function were collected. Associations between eGFR and clinical prognosis were assessed using multivariate Cox proportional hazards regression models. The impact of eGFR on the recurrence was evaluated by logistic and Poisson regression models. Odds ratios are reported for associations between eGFR and recurrence and prognosis. Stratified analyses and restricted cubic splines (RCS) were used to evaluate the results between subgroups and nonlinear relation between eGFR and the prognosis and recurrence of patients with CRC.Results93 CRC patients completed the study. Poor renal filtration function and impaired urine concentrating ability were found in CRC patients. Multivariate analysis showed that eGFR was an independent predictor of clinical prognosis (eGFR < 90 mL/min OR=4.248, 95% CI [1.061-17.003], P=0.041, the eGFR of 90–110 mL/min OR=5.087, 95% CI [1.268-20.400], P=0.022) when using the eGFR ≥ 130 mL/min as the reference. Multivariate analysis showed that eGFR (OR=0.964, 95% CI [0.933-0.997], P=0.032) was an independent protective factor influencing recurrence of CRC patients. RCS analysis showed that the relationship between eGFR and prognosis of CRC patients had no significant nonlinear correlation (P for nonlinear=0.19), the relationship between eGFR and recurrence was non-linear (P for nonlinear<0.001).ConclusionsCRC patients exhibited kidney dysfunction, and eGFR is identified as an independent predictor of disease recurrence and prognosis.